Discovering Political Ecology - Gustav, Cederlöf; Loftus, Alex (London Routledge, 2024)
Political ecology is one of the most vibrant fields of environmental research. This book introduces political ecology to a new generation of students in a daring new way: as an interdisciplinary approach to environmental research but also as a series of lived realities and a praxis for change.
Keywords: Environment & the Global South; Political Ecology; Environmental Geography